Developing multichannel marketing - Maklan, Stan (Henry Stewart Talks, 2008)
Analysis, Understanding sales complexity, Current and future coverage mapping, Current and future channel chains, Assessing channel chains, Cost analysis, Prioritization matrix, Implementation
Archived at 2022/03/17